Self-efficacy, Social Support and Self-management in Thalassemic Adolescents - Sridan, Wasun; Jintrawet, Usanee; Niyomkar, Srimana (Nursing Journal CMU, 2021)
Proper self-management in adolescents with thalassemia will lead to good health outcomes and proceed to productive adults. The objective of this descriptive research was to investigate self-management, and the relationship between self-efficacy, social support and self-management in thalassemic adolescents. The conceptual framework is based on self-management concept by Schilling, Grey, & Knafl, (2002); Schilling et al., (2009) and a review literature. Eighty five adolescents with thalassemia (15 to 17 years old) were purposively recruited from the pediatric out-patient department or the hematology clinic of three tertiary hospitals, northern Thailand. The research instruments included the self-efficacy in adolescents with thalassemia scale, the social support in self-management in adolescents with thalassemia scale, and the self-management in adolescents with thalassemia scale. The content validity index (CVI) of these questionnaires were .90, 1.00 and 1.00, respectively. The reliability showed acceptable value of 0.74, 0.72 and 0.81, respectively. Data were collected from July to October 2017, and were analyzed using descriptive statistics and the Spearman’s rank correlation coefficient. The results were as follows: 1. Adolescents with thalassemia of 81.18 % showed the mean score of self-management at a high level (x = 69.72, S.D. = 8.31). 2. Self-efficacy and social support were statistically significant moderate positive relationship with self-management in adolescents with thalassemia (r = .49, p < .001, r = .45, p < .001, respectively). The findings of this study serve as the preliminary data for related health personnel, nurses in particular, to effectively promote self-management in adolescents with thalassemia that may increase quality of life and reduce further complications.